Aktiebolagsstyrelsens personliga ersättningsansvar vid olovliga värdeöverföringar - Särskilt om förhållandet mellan bristtäckningsansvaret i 17 kap. 7 § ABL och skadeståndsansvaret i 29 kap. 1 § ABL - Wärmlind,Saga (2025)
A characteristic feature of the limited liability company as a form of association is that neither shareholders nor directors of the board are personally liable for the company’s obligations. Only the company’s own assets can therefore be used to pay its debts. In order to balance the limited personal liability against creditors’ interest in receiving payment for their claims, Chapter 17 of the Swedish Companies Act (2005:551) (ABL) contains provisions that limit the company’s right to gratuitously reduce its assets. A transfer of value that contravenes the capital protection rule in Chapter 17, Section 3 ABL is un-lawful and may be reclaimed from the recipient through a restitution claim under Chapter 17, Section 6 ABL. If the unlawfully transferred value cannot be fully or partially recovered from the recipient, directors of the board who participated in the transfer may be held personally liable for the deficiency pursuant to Chapter 17, Section 7 ABL. Provisions prescribing personal liability for directors are also found in the damages provision in Chapter 29, Section 1 ABL, which prescribes both internal liability towards the company and external liability towards its creditors. In light of the above, this essay aims to investigate and analyse the personal liability of the board of directors of a limited liability company in the event of unlawful value transfers. The investigation focuses partly on liability for deficiency under Chapter 17, Section 7 ABL, and partly on liability for damages under Chapter 29, Section 1 ABL. A central part of fulfilling this purpose lies in analysing the relationship between these two liability provisions. The investigation shows that members of the board can be held personally liable under both Chapter 17, Section 7 and Chapter 29, Section 1 ABL in the event of an unlawful transfer of value, provided that the requirements in each provision are met in the individual case. The investigation also shows that the scope of these liabilities may differ. The deficiency liability is limited to the unlawfully transferred value, while liability for damages may include all damage that the unlawful transfer of value has caused the company. In relation to individual creditors, board members can only be held liable for damages under Chapter 29, Section 1 ABL. The investigation also shows that the creditors’ possibilities of asserting such a claim are very limited. Regarding board members’ liability to the company, the investigation shows that the two liability provisions are applicable in parallel. The practical significance of this is that the company or its rights holders can claim deficiency liability under Chapter 17, Section 7 ABL for the unlawfully transferred value, and liability for damages pursuant to Chapter 29, Section 1 ABL for the excess damage caused to the company by the unlawful value transfer.
Keywords: associationsrätt; aktiebolagsrätt; förmögenhetsrätt; skadeståndsrätt